A real-time fluorescent reverse transcription quantitative PCR assay for rapid detection of genetic markers’ expression associated with Fusarium Wilt of banana biocontrol activities in bacillus - Li, Shu; He, Ping; Fan, Huacai; Liu, Lina; Yin, Kesuo; Yang, Baoming; Li, Yongping; Huang, Su-Mei; Li, Xundong; Zheng, Si-Jun (MDPI, 2021)
Fusarium wilt of banana, caused by Fusarium oxysporum f. sp. cubense (Foc), especially Tropical Race 4 (TR4), seriously threatens banana production worldwide. There is no single effective control measure, although certain Bacillus strains secrete antibiotics as promising disease-biocontrol agents. This study identified five Bacillus strains displaying strong antibiotic activity against TR4, using a systemic assessment for presence/absence of genetic markers at genome level, and expres sion profiles at transcriptome level. A conventional PCR with 13 specific primer pairs detected biocontrol-related genes. An accurate, quantitative real-time PCR protocol with novel designed specific primers was developed to characterise strain-specific gene expression, that optimises strain culturing and RNA-isolation methodologies. Six genes responsible for synthesising non-ribosomal peptide synthetase biocontrol metabolites were detected in all five strains. Three genes were involved in synthesising three Polyketide synthetase metabolites in all five strains, but the macrolactin synthase gene mln was only detected in WBN06 and YN1282-2. All five Bacillus strains have the genes dhb and bioA, essential for synthesising bacillibactin and biotin. However, the gene sboA, involved in subtilisin synthesis, is absent in all five strains. These genes’ expression patterns were significantly different among these strains, suggesting different mechanisms involved in TR4 biocontrol. Results will help elucidate functional genes’ biocontrol mechanisms.